Psychometric Properties Of Moral Intelligence And Proactive Decision-Making Instrument - Raheem Shiltagh, Al Saedi Hazim (2019)
Good Psychometric properties of moral intelligence and proactive decision-making are crucial in infusing accuracy and precision in drawing accurate conclusions about university students. This study aims at examining the psychometric properties of the validity of moral intelligence and proactive decision-making and the relationship. The research is quantitative, and it employs a survey research design. The sample consists of nine hundred and ten (910) university students in Iraq. Analyses suggest that the moral intelligence and proactive decision-making scales are reliable, valid and psychometrically sound according to Rasch principles.